Microbiological Quality Analysis and Identification of Lactic Acid Bacteria from the Product of Fermentation of Mackerel - Sukmawati Sukmawati (UNIVERSITAS NEGERI PADANG, 2024)
Mackerel is a type of fish that has high nutritional value, this fish is a source of protein and is in great demand by many people. Mackerel can be processed into various types of processed food, one of which is through the fermentation process. The purpose of this study was to determine the microbiological quality, to determine the characteristics and the number of lactic acid bacteria , and to identify the species of lactic acid bacteria found in the fermented mackerel product. The results showed that the microbiological test of mackerel fermented products had the highest total plate number (ALT) in the Fit.L sample, namely 4.2x105 cfu/g, followed by the Fit.C sample with a value of 2.4x104 cfu/g, and the lowest value was in the Fit. A sample 4.3x103 cfu/g. The total plate number (ALT) in each test sample stated that the number did not exceed the maximum limit of the Indonesian national standard. Microbiological test results through the E.coli estimator test of the three samples showed a value of <3 APM/g, then the reinforcement test results were declared not to contain E.coli bacteria.The number of lactic acid bacteria (LAB) present in the mackerel fermented product sample showed the highest value in the Fit.L sample, namely 1.8x104 cfu/g, then in the Fit.C sample with a value of 2.6x103 cfu/g, while the lowest was in the Fit. A sample whose value is 3.6x102 cfu/g. The morphological characteristics of the LAB colonies from the three samples showed the same characteristics, namely round shape, smooth edges and convex elevation. The results of the identification of the two isolates from the two samples stated that the Fit.A isolate was identified as Staphylococcus condimenti strain DSM 11674 and the Fit.C isolate was identified as Lactobacillus reuteri strain 1444